A TENSÃO CAMPO-CIDADE NO ADVENTISMO BRASILEIRO: MUDANÇA NO DISCURSO INSTITUCIONAL E REINTERPRETAÇÃO DE UMA TRADIÇÃO RELIGIOSA - LIMA, WENDEL THOMAZ (2020)
Present in Brazil since the end of the 19th century, the Seventh-day Adventist Church (IASD) has reformulated its discourse on cities in recent decades, moving from an anti-urban stance to an attitude of encouraging presence and intervention in the metropolises. Based on studies in the sociology of religious memory, this research seeks to identify reinterpretations of the writings of Ellen G. White, co-founder of the denomination. It appears in these writings an ambivalent thought in relation to cities. Now advising that Adventists and church institutions were not in the metropolis, because of the risks to health, morality and fearing the future judgments of God, now appealing for the urban centers of their time to be evangelized. In this study, we compared the advice of the Adventist pioneer published in two posthumous compilations, Vida no Campo (1966) and Ministério Para Cidades (2012). We verify how these books echoed in institutional documents and Adventist publications, thus evidencing a rural-city tension in this religious tradition and that a reinterpretation of elements of its founding memory is underway.